Development of an computational algorith for estimating cables´tensile stress on cable-stayed bridges based on experimental laboratory and job site measurements on their natural vibration modes and frequencies - Muñoz, Edgar; Avellaneda, Giordano; Noguera, Ricardo (Revista Ingeniería de Construcción, 2012)
In the present research, is proposed a new methodology for estimating tension forces in cables on the basis of their modes and natural frequencies of vibration, by developing a computer application leaning on the finite element method (FEM) and a detailed analysis of signals. In this paper is presented a state of the art with some of the work done around the world, a conceptual framework and a proposed methodology for its development and implementation. The computer application which was programmed in MATLAB ®, which was validated through experimental measurements on a scaled prototype and some cables of a cable stayed bridge under construction in Colombia, allows to estimate the magnitude of the cable’s tension with minimal errors.